Significance of the mathematically calculated red cell indices in patients with qualitative and quantitative hemoglobinopathies - Heba A. Ahmed; Safaa A. A. Khaled; Eman M. Fahmy; Nesreen A. Mohammed; Hamdy F. F. Mahmoud (SpringerOpen, 2022)
Abstract Background Hemoglobinopathies represent a set of inherited red blood cell (RBCs) disorders, characterized by abnormal hemoglobin molecule. They include qualitative and quantitative hemoglobinopathies, with a structurally abnormal globin chain in the first and defective production in the later. This study assessed, for the first time, the significance of the mathematically calculated RBC indices to identify patients with hemoglobinopathies from normal subjects or iron deficiency anemia (IDA) and to differentiate various types of hemoglobinopathies from each other. Subjects and methods The study was a comparative hospital based and included 167 participants with hemoglobinopathies (group 1) and 49 participants with IDA (group 2) as an active comparator. Another 50 healthy volunteers (group 3) were also included. All participants were subjected to medical history, clinical examination, CBC, and HPLC. Next, 10 RBC indices were mathematically calculated from the CBC for each participant. Results Gender analysis shows that females represent 36.8% in thalassemia group, 42% in sickle cell disease (SCD) group, and 71.4% in IDA group. The receiver operating characteristic (ROC) curve shows that Ehsani index (EI) is the most reliable screening tool for thalassemics because of showing the highest Youden index and specificity of 41.88% and 88.89%, respectively, followed by Shine and Lal index (SL), with Youden index (YI) value, specificity, and sensitivity equal to 39.78%, 69.70%, and 70.09%, respectively. Similar results were found for IDA. For SCD, SL index is the most suitable screening tool. In conclusion, the mathematically calculated RBC indices are available, cheap, reliable, and sensitive tools for screening patients with hemoglobinopathies.